THE INFLUENCE OF DIGITAL MARKETING TRAINING AND FINANCIAL REPORTS ON GARAGE SALE ONLINE EVENT (CASE STUDY AT PRE ENTREPRENEURIAL CENTER IN BANDUNG) - Gita Genia Fatihat; R Susanto Hendiarto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to know the description of each variable, and how strong the influence of digital training on marketing and financial reports on online garage sale events at Pre Entrepreneurial Center in Bandung. The sample collection technique was carried out purposively, given the uniqueness and features of this sale. This study examines two variables, namely digital training as the independent variable, and online garage sale as the dependent variable. While the method used in this research is descriptive quantitative method. The data collected is in the form of primary data. Meanwhile, the data collection technique is through library research and field research. The results of this study describe that the public interest and enthusiasm for the implementation of digital training is very high, especially marketing and financial reports, as well as the enthusiasm and passion of respondents for online garage sale events have a high perception, the digital training variable has a significant and significant effect on the garage sale event variable. online at the PreEntrepreneurial Center locus, and the determinant coefficient shows a high percentage so that the influence of the independent variable on the dependent variable is very strong. The online Garage sale event has a high magnitude and level of differentiation, is easy to implement, does not require capital, but instead is a new breakthrough solution to raise capital, does not require space, but can create a marketplace. This event has the potential to create new entrepreneurial centers. So that the implications for society will be multi-use and multiplier effect, so that the existence of digital training must be supported by the government, society and the business world, research must be developed to find out other variables that affect online garage sale events.